Gaining Organizational Adoption: Strategically Pacing the Position of Digital Innovations - Karp, Rebecca (Academy of Management Journal, 2023)
Scholars have long suggested that, to foster adoption for their innovations, entrepreneurs should engage with customers to better understand their unmet needs. Yet, customers frequently reside in organizations, and organizational members may not be aligned in their views regarding the benefits an innovation offers. Decision-making within organizations is rarely under the purview of a single executive and various members can wield influence. Given this plurality, how do entrepreneurial firms gain organizational adoption for their innovations? I explore how 54 entrepreneurial firms, all participating in a digital health accelerator, attempted to gain organizational adoption for their innovations. I show that, when entrepreneurs pursued an embedded process, they developed ways to expand the relevance of their innovations for new customers through new use cases, but strategically paced and withheld disruptive aspects of their innovations to appease different audiences within customer organizations. Firms that leveraged a market-centric process also expanded the relevance of their innovations. Despite sparking the interest of executives, firms using a market-centric approach did not gain adoption. By unpacking the process by which some entrepreneurs discovered how to strategically pace the deployment of their digital innovations, I contribute a mechanism that explains how digital innovations gain organizational adoption.